2016
DOI: 10.1063/1.4960583
|View full text |Cite
|
Sign up to set email alerts
|

Spiral growth of few-layer MoS2 by chemical vapor deposition

Abstract: Growth spirals exhibit appealing properties due to a preferred layer stacking and lack of inversion symmetry. Here, we report spiral growth of MoS2 during chemical vapor deposition on SiO2/Si and epitaxial graphene/SiC substrates, and their physical and electronic properties. We determine the layer-dependence of the MoS2 bandgap, ranging from 2.4 eV for the monolayer to a constant of 1.3 eV beyond the fifth layer. We further observe that spirals predominantly initiate at the step edges of the SiC substrate, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 34 publications
4
30
0
Order By: Relevance
“…The CBM of TMDs is dominated by d-states of the transition metal atom sandwiched between chalcogen atoms and is therefore less sensitive to number of layers than the VBM. Based on this measurement, the resulting WS 2 bandgap is approximately 1.78 eV and is in good agreement with the bandgap measured by scanning tunneling spectroscopy (STS) of 3L MoS 2 which is known to have a very similar electronic band structure 1,2,24 .…”
supporting
confidence: 79%
“…The CBM of TMDs is dominated by d-states of the transition metal atom sandwiched between chalcogen atoms and is therefore less sensitive to number of layers than the VBM. Based on this measurement, the resulting WS 2 bandgap is approximately 1.78 eV and is in good agreement with the bandgap measured by scanning tunneling spectroscopy (STS) of 3L MoS 2 which is known to have a very similar electronic band structure 1,2,24 .…”
supporting
confidence: 79%
“…SDD growth mechanism is preferred at lower supersaturation where threading dislocations, such as slipped planes at the basal domain with a screw component present on the surface providing a continuous step source, can lead to a spiral-like growth. Spiral-like growth has been predicted by Burton, Cabrera, and Frank (BCF theory) in their pioneering theoretical work 38 , and has been observed for the different transition metal chalcogenide systems 30,[40][41][42] . Presence of such spiral-like growth on a triangular domain is shown in Fig.…”
mentioning
confidence: 85%
“…However, they concluded that a large variation exists between different samples of exfoliated MoS2 and that is necessary to find a synthesis route for obtaining high quality MoS2. So far, STM characterization of the defects in CVD grown MoS2 was mostly confined to the study of point defects and grain boundaries in rotationally commensurate epitaxial graphene/MoS2 system 28,29 and spiral growths 30 .…”
mentioning
confidence: 99%
“…At first glance, the spirals' growth behavior in Bi-based TI systems might be considered to come from misfit dislocations at the interface during epitaxial growth, as in conventional semiconductor systems [104][105][106], where the spirals are often considered to come from misfit dislocations at the interface during heteroepitaxial growth. When the dislocations have a screw component, they can emerge at the surface to form additional steps to facilitate the growth of spirals.…”
Section: Surface Passivation and Surface Morphologymentioning
confidence: 99%